Randomized controlled trial comparing low pressure (8 mmHg) versus high pressure (14 mmHg) CO2 insufflation on postoperative pain in patients undergoing laparoscopic cholecystectomy: Protocol - Amine Ben Safta; Salsabil Nasri; Imen Samaali; Hajer Taher; Mohamed Mehdi Trabelsi; Chadli Dziri; Wajih Dougaz; Ramzi Nouira (PLoS ONE, 2025)
Background Laparoscopic cholecystectomy is the gold standard for treating symptomatic gallstone disease. Pneumoperitoneum is essential for adequate visualization during the procedure and is typically maintained at a standard pressure of 12–14 mmHg. However, high insufflation pressure may contribute to increased postoperative pain. This study aims to assess whether low-pressure pneumoperitoneum (8 mmHg) reduces postoperative pain compared to standard pressure (14 mmHg), without compromising operative safety or efficacy. We hypothesize that low pressure pneumoperitoneum at 8 mmHg reduces postoperative pain, without increasing operation time or postoperative morbidity. Methods This is a single-center, randomized, controlled, double-blind trial. Consecutive Adult patients scheduled for elective laparoscopic cholecystectomy will be randomized in a 1:1 ratio to receive either low-pressure (8 mmHg) or standard-pressure (14 mmHg) pneumoperitoneum. The primary outcome is postoperative abdominal pain assessed using the Visual Analog Scale (VAS) at 6 hours after surgery. Secondary outcomes include VAS pain scores at 12 and 24 hours, postoperative nausea and/or vomiting, postoperative hospital stay and postoperative 30-day morbidity. The enrollment of patients will be done between November 12, 2024 to December 31, 2025. Trial registration ClinicalTrials.gov NCT06685250 Conclusion If proven effective, low-pressure pneumoperitoneum may represent a simple strategy to improve postoperative comfort in laparoscopic cholecystectomy without compromising surgical outcomes.